Тренінг комунікативної компетентності як форма соціально-мовленнєвої взаємодії майбутніх соціальних працівників у процесі вивчення курсу "Основи комунікації в соціальній роботі" - Равлюк, Тетяна; Куб'як, Наталія (My University, 2018)
In the process of qualitative training of creative specialists in higher education institutions, they are motivated to continuous professional development, the problem is the development and improvement of communicative competence, creative potential, and enhancement of the culture of oral and written speech. The implementation of these tasks is possible in the context of mastering the skills of future social workers by the skill of the word in the process of studying professionally oriented disciplines, in particular, "Fundamentals of communication in social work", "Training of the formation of communicative skills". The purpose of the article is to justify the importance of training work in forming the communicative competence of future social workers in the course of studying the course "Fundamentals of communication in social work". In the choice of forms, methods of work that contribute to the formation of communicative competence of students, the results of the survey of teachers of the Department of Pedagogy and Social Work of Yuriy Fedkovych Chernivtsi National University, social educators and social workers of Chernivtsi were taken into account. Analysis of the results of the study has showed that the most effective among them is the preparation and conducting of trainings (72.40%), non-standard social activities (54.94%), organization of meetings with social specialists (49.65%), preparation and conducting of business games (49,03%), round tables on actual social topics (44,38%), conversations with different categories of clients (41,18%), discussions (36,3%), press conferences (35,7 %). Examples of training exercises that form the skills of verbal and non-verbal communication of future social workers in the process of studying the course "Fundamentals of Communication in Social Work" ("Our Names", "Gift", "Gamer", "Strategies of Conduct in Conflict and ways to solve it") are given
Keywords: competence; communicative competence; social psychological training; training